The complete idiot's guide to European history - Barber, Nathan, 1971- (New York, N.Y. : Alpha Books, 2011)
Geared towards AP History students or anyone interested in history, this updated guide provides easy-to-understand facts covering hundreds of years of European history in the areas of culture, economy, politics and social history.
Includes bibliographical references and index.
Keywords: Middle Ages; History, Modern; Europe -- History